Four-Chamber Intracardiac Thrombi Complicating Wild-Type TTR Amyloidosis - Jan M. Griffin; Daniel P. Judge; Kenton J. Zehr; Jose Madrazo; Rosanne Rouf (Case Reports in Cardiology)
Cardiac amyloidosis is a rare disease, and its prevalence varies depending on the type of amyloid protein involved. Several case reports make reference to the increased risk of thrombosis and thromboembolic events in cardiac amyloidosis. We report a case of rapidly evolving, multichamber thrombi in a patient who was ultimately diagnosed with wild-type TTR cardiac amyloidosis.